1999
DOI: 10.1007/s004410051370
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of endothelial wound repair: conversion of quiescent to migrating endothelial cells involves tyrosine phosphorylation and actin microfilament reorganization

Abstract: Endothelial repair to reestablish structural integrity following wounding is a complex process. Since the actin cytoskeleton undergoes specific changes in distribution as quiescent endothelial cells switch to activated migrating cells over a 6-h period following wounding (Lee et al. 1996), we studied tyrosine phosphorylation in association with actin microfilaments and adhesion proteins using double immunofluorescent confocal microscopy. We showed that in a confluent monolayer phosphotyrosine localized at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…46,47 Myofibroblast ␣-SMA expression and its assembly into stress fibers are important in cell migration, force generation, and wound contracture both in vitro and in vivo. 48,49 In our model it is likely the increased stress fibers at the WE is associated with elongation and migration of the VICs into the wound.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Myofibroblast ␣-SMA expression and its assembly into stress fibers are important in cell migration, force generation, and wound contracture both in vitro and in vivo. 48,49 In our model it is likely the increased stress fibers at the WE is associated with elongation and migration of the VICs into the wound.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (9,57,63,64) have shown a correlation between increased phosphorylation of TJ proteins (ZO-1, ZO-2, and occludin) and increased permeability in both kidney and brain cell culture models. Indeed, it has been suggested that changes in phosphorylation of these cellular proteins is responsible for perturbations in cell-to-cell adhesion (40,63). Whereas a 2.3-fold increase in tyrosine phosphorylation was seen in aortic endothelial cells exposed to 4-h hypoxia with 30-s posthypoxic reoxygenation (12), it is not clear which proteins are phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…trans-Resveratrol significantly inhibits the ability of GM7373 cells ( Fig. 2A) and MAECs (data not shown) to repair a wounded monolayer, a phenomenon that depends on the migratory and proliferative activity of the cells at the edge of the wound (32). Also, as shown in Fig.…”
Section: In Vitro Effects Of Resveratrol Stereoisomers On Different Smentioning
confidence: 97%